CT and 3-T MRI accurately identify T3c disease in colon cancer, which strongly predicts disease-free survival. Issue 4 (April 2017) - Hunter, C.; Siddiqui, M.; Georgiou Delisle, T.; Blake, H.; Jeyadevan, N.; Abulafi, M.; Swift, I.; Toomey, P.; Brown, G.
Abstract : Aim: To compare the preoperative staging accuracy of computed tomography (CT) and 3-T magnetic resonance imaging (MRI) in colon cancer, and to investigate the prognostic significance of identified risk factors. Materials and methods: Fifty-eight patients undergoing primary resection of their colon cancer were prospectively recruited, with 53 patients included for final analysis. Accuracy of CT and MRI were compared for two readers, using postoperative histology as the reference standard. Patients were followed-up for a median of 39 months. Risk factors were compared by modality and reader in terms of metachronous metastases and disease-free survival (DFS), stratified for adjuvant chemotherapy. Results: Accuracy for the identification of T3c+ disease was non-significantly greater on MRI (75% and 79%) than CT (70% and 77%). Differences in the accuracy of MRI and CT for identification of T3+ disease (MRI 75% and 57%, CT 72% and 66%) and N+ disease (MRI 62% and 63%, CT 62% and 56%) were also non-significant. Identification of extramural venous invasion (EMVI+) disease was significantly greater on MRI (75% and 75%) than CT (79% and 54%) for one reader ( p =0.029). T3c+ disease at histopathology was the only risk factor that demonstrated a significant difference in rate of metachronous metastases (odds ratio [OR] 8.6, p =0.0044) and DFS stratified for adjuvant therapy (OR=4, p =0.048). Conclusion: T3c or greater disease is the strongest risk factor for predicting DFS in colon cancer, and is accurately identified on imaging. T3c+ disease may therefore be the best imaging entry criteria for trials of neoadjuvant treatment. Highlights: T3c or greater disease is the adverse feature most reliably identified on imaging. T3c or greater disease on histopathology predicts significantly worse DFS. Accuracy for identification of adverse features was similar on CT and 3T MRI.